PENDUDUK DAN KEBUTUHAN PANGAN DI INDONESIA 2005-2050: SUATU PROYEKSI - Rachmini Saparita (LPPM Universitas Terbuka, 2006)
The aim of this study was to identify population growth during 1960-2002, and also its projection until 2050. The study also analyzed its impact and look for alternative policies in overcoming the problem to fulfill food security. The model used in the study was dynamic system approach which analyzes previous events to predict the upcoming condition. The study result indicated that the population increased rapidly, and was predicted would continue growing fast. Population growth and food requirement per capita determined the level of requirement of total food. To reach food security, the requirement would be better fulfilling by domestic production and did not depend on import. The policy alternative, which consisted of farm harvest enlargement and technological adoptions, were proposed to meet domestic production exceeding the requirement.